SELFIE BEHAVIOR.THE MODERATING ROLE OF PERSONALITY - Leonilan, Leonilan; Girsang, Bastian R; Anindita, Tasya Julia (REVENUE: Jurnal Manajemen Bisnis Islam, 2020)
This study aimed to investigate the effect of selfie behavior to individual performance with extrovert personality as a moderating variable. Inconsistence result of the past research on narcissism topic is a uniqueness gap for this research. Previous research finding a positive and negative effect of selfie behavior to outcome. In this research we including personality as a moderating variable to clearly the result of selfismeffect to individual outcome. The other research gap is from the research sample. We using Gen.Z for the sample because that’s is under research and Gen. Z very closely with “selfie phenomena”. The study was conducted with 100 respondents. The sample technique of this research is non-probability sampling with purposive sampling technique. Sample of this research is Generation Z that’s based on previous research is under research. We have to test validity (face validity and factor loading) &reliability (cronbach’s alpha, AVE, and composite reliability) before hypothesis testing. We using a Partial Least Square 3 (PLS) for solve measurement of this research. The findings of the research is supported to hypothesis 1 that selfie behavior give a positive impact to individual performance. Hypothesis 2 is too supported that extrovert strength the relationship selfie behavior and individual performance. The conclusion that clarify the inconsistence previous research, that selfie behavior give a positive impact to individual performance, and extrovert strengthen relationship selfie behavior and individual performance.